High rates of undiagnosed hypoalbuminaemia in orthopaedic trauma patients at a rural hospital - Maimin, Dane Gary (Division of General Surgery, 2025)
Background: The deleterious effects of hypoalbuminaemia in the peri-operative period are well documented. We aimed to review serum albumin levels in a cohort of orthopaedic trauma patients to determine the prevalence of hypoalbuminaemia. Secondarily, we aimed to identify factors associated with an increased risk of hypoalbuminaemia. Methods: A retrospective cross-sectional study was performed of data collected prospectively at a regional hospital serving primarily a rural population in South Africa. Results Two hundred ninety-five patients were included in the study. Twenty-nine per cent of the cohort was found to have hypoalbuminaemia. Femur neck fractures (p < 0.001), intertrochanteric fractures (p = 0.004), tibial plateau fractures (p = 0.034) and polytrauma (p = 0.013) were associated with hypoalbuminaemia. The mean albumin level was lower in HIV-positive patients when compared to HIV-negative patients (35.7 g/L vs 37.5 g/L, p = 0.007). The presence of comorbidities other than HIV, like diabetes mellitus (p = 0.001), previous pulmonary tuberculosis (p = 0.034) and chronic renal failure (p = 0.007) was associated with hypoalbuminaemia. Conclusion: In this cohort of orthopaedic trauma patients from rural South Africa, we found a 29% prevalence of hypoalbuminaemia at the time of presentation. High-risk subgroups include patients with pre-existing comorbidities and increased age, as well as patients presenting with polytrauma, femoral neck, intertrochanteric femur or tibial plateau fractures.